A theory of the executive branch : tension and legality - Cohn, Margit (Oxford University Press, 2021)
This monograph offers a theoretical foundation of the executive branch in Western democracies and argues that the tension between dominance and submission is maintained by the adoption of various forms of fuzziness, under which a guise of legality masks the absence of the substantive limitation of power.